1986
DOI: 10.1080/00288330.1986.9516173
|View full text |Cite
|
Sign up to set email alerts
|

Depth distribution and abundance of benthic organisms and fishes at the subtropical Kermadec Islands

Abstract: Subtidal areas of the Kermadec Islands have not previously been described; samples from a bay at Raoul Island are discussed here. Abundances and percentage cover of benthic organisms were assessed from the high intertidal to 20 m depth using quadrat sampling. Fish abundances were assessed subtidally by random transects in shallow (3-6 m deep) and deep (14-20 m) areas of the reef. Hard corals occurred at 2-18 m depths at densities of 5 colonies per m 2 , but colonies were generally small. Soft coral colonies oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 34 publications
8
53
0
Order By: Relevance
“…Parma polylepis has previously been reported from the Kermadec Islands by Paulin & Stewart (1985) and Schiel et al (1986). Francis et al (1987) have shown that those reports were based on misidentifications of the recently described and morphologically similar P. kermadecensis (though Allen (1987) was apparently unaware of the reports and did not include them in the synonymy of P. kermadecensis).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Parma polylepis has previously been reported from the Kermadec Islands by Paulin & Stewart (1985) and Schiel et al (1986). Francis et al (1987) have shown that those reports were based on misidentifications of the recently described and morphologically similar P. kermadecensis (though Allen (1987) was apparently unaware of the reports and did not include them in the synonymy of P. kermadecensis).…”
Section: Discussionmentioning
confidence: 93%
“…Parma kermadecensis is endemic to the Kermadec Islands, where it is common to abundant (Allen 1987;Francis et al 1987). Parma polylepis Gunther, 1862 was reported from the Kermadec Islands by Paulin & Stewart (1985) and Schiel et al (1986), but their reports were based on misidentified P. kermadecensis (Francis et al 1987). Therefore there are currently no valid reports of P. polylepis from New Zealand waters.…”
Section: Introductionmentioning
confidence: 98%
“…Some of those areas may also have abundant laminarian macroalgae (e.g., Houtman Abrolhos- Hatcher & Rimmer 1985;Solitary Islands-Veron et al 1974;Harriot et al 1994). Subtropical areas described to date mainly harboured browsing piscine herbivores such as kyphosids and girellids, although herbivorous pomacentrids also occur (e.g., Schiel et al 1986;Cole et al 1992;Francis 1993Francis , 1996. Kyphosid and girellid fishes may be abundant (Hatcher & Rimmer 1985;Schiel et al 1986; review of Choat 1991;Cole et al 1992), but patterns of abundance along depth gradients are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The geography, geology, and biogeography of these groups have been reviewed by Hoggett & Rowe (1988), Francis (1993), and Brook (1998a). Kermadec Islands are one of the more thoroughly described of the subtropical areas (Nelson & Adams 1984;Schiel et al 1986;Francis et al 1987;Cole et al 1992;Francis 1993Francis , 1996Brook 1998aBrook ,b 1999. Kermadec Islands possess a flora of inconspicuous macroalgae (Nelson & Adams 1984;Schiel et al 1986) and a limited fauna of scleractinian corals (Brook 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation